Social Innovation for BUMDES Bicak Makmur: Sustainable Partnerships in Local Crafts Production and Marketing - Tatas Ridho Nugroho; Tomy Rizky Izzalqurny; Muhammad Fuad; Riska Dwi Aprilia; Nabila Aura Dewanti (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This activity aims to enhance economic independence in Bicak Village by developing local craft products from regional resources, focusing on products like knitted bags and accessories made from unique natural materials. Method: The program employs a community partnership empowerment approach, including observation, training in production and management, and support in website creation and digital marketing to enhance local skills in production, management, and marketing. Practical Applications: Activities include socialization and training in efficient raw material utilization and creative enhancement, financial management, website development, and digital marketing. These efforts improved production quality dan marketing capabilities, enabling participants to expand their market reach through digital platforms effectively. Conclusion: Bicak Village faces challenges in expanding market reach for local crafts and limited production and material management skills. This community service program provides solutions through training in production, management, and digital marketing via social media.